Etiology, pathophysiology and treatment of ankyloglossia in babies and its effect on breastfeeding - Bukhsh, Ayman T.; Almohammadsaleh, Anfal A.; Alzahrani, Abdullah M.; Murshed, Raghad A.; AlHubayshi, Abdullah A.; Alsadiq, Sarah M.; Shaik, Fatimah A.; Alboeid, Atheer A.; Alsumur, Ahmed M.; Alsolami, Abdulsalam F.; Aljuhani, Thoraya E. (International Journal Of Community Medicine And Public Health, 2023)
The lingual frenulum inhibits tongue mobility in ankyloglossia, sometimes referred to as tongue-tie. It affects 4–16% of babies, with boys being more likely to be affected. Anterior and posterior tongue ties are the two primary forms. When a newborn opens their mouth, anterior tongue ties are easy to spot because they look like a heart; posterior tongue ties are trickier to spot. Ankyloglossia can make it difficult to nurse, speak clearly, maintain good oral hygiene, or engage in other oral activities. Tongue-tie can influence a baby’s oral development as well as the way he or she feeds, talks, and swallows. It is crucial to diagnose ankyloglossia through a thorough examination. Treatment options include lactation consultation, improving latch during breastfeeding, and a procedure called frenotomy, which involves releasing the frenulum. Research is ongoing to establish evidence-based recommendations and standardized diagnostic criteria for ankyloglossia. This review will focus on etiology, pathophysiology and treatment of ankyloglossia in babies and its effect on breastfeeding.